IMPLEMENTATION OF THE IMPOSITION OF RESTRICTIONS ON EMERGENCY COMMUNITY ACTIVITIES FOR CORONA VIRUS DISEASE (PPKM) IN RELATION TO POSITIVE LAW IN INDONESIA - Elvira Fitriani Pakpahan; Tommy Leonard; Darwis Darwis (Magister Kenotariatan Universitas Pasundan, 2021)
This study aims to analyze the legal basis for implementing Emergency PPKM and sanctions if the community violates Emergency PPKM. This research is a type of normative juridical law research. To obtain the data needed in this study, literature research was used and then analyzed qualitatively by collecting primary, secondary and tertiary legal materials related to research. Based on the results of data analysis, the results obtained: The legal basis for implementing Emergency PPKM based on the perspective of the Government of the Republic of Indonesia is the Law of the Republic of Indonesia Number: 4 of 1984 concerning Outbreaks of Infectious Diseases in Article 1 to Article 6 while sanctions are regulated in Article 14 paragraph (1) to paragraph (3) and the Law of the Republic of Indonesia Number: 6 of 2018 concerning Health Quarantine in Article 9 while sanctions are only given to the captain, pilot captain and person in charge of land transportation with the overall implementation regulated in government regulations where government regulations are statutory regulations determined by the President to carry out the law properly, The benefits of the Emergency PPKM being implemented are to suppress the spread of the covid-19 virus in certain activities or in non-essential activities as a form of follow-up to the direction of the President of the Republic of Indonesia because people do not understand the importance of implementing health protocols so that there is an increase in people exposed to the corona virus every day, The sanctions given if the public violates the Emergency PPKM do not have a strong legal basis and the issuance of the Instruction of the Minister of Home Affairs is not appropriate because Indonesia is still in a state of emergency based on Presidential Decree Number: 11 of 2020 concerning the Determination of the Covid-19 Public Health Emergency so that emergency handling must refer to Presidential Decree Number: 11 of 2020 concerning the Determination of the Covid-19 Public Health Emergency or through a Government Regulation.